2020
DOI: 10.3390/cells9030656
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle Cell-Specific Progerin Expression Provokes Contractile Impairment in a Mouse Model of Hutchinson-Gilford Progeria Syndrome that Is Ameliorated by Nitrite Treatment

Abstract: Cardiovascular disease (CVD) is the main cause of death worldwide, and aging is its leading risk factor. Aging is much accelerated in Hutchinson-Gilford progeria syndrome (HGPS), an ultra-rare genetic disorder provoked by the ubiquitous expression of a mutant protein called progerin. HGPS patients die in their teens, primarily due to cardiovascular complications. The primary causes of age-associated CVD are endothelial dysfunction and dysregulated vascular tone; however, their contribution to progerin-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…Reduction of DNA repair capacity by targeted mutation of Lmna in VSMC, the gene that is responsible for accelerated-aging in Hutchinson–Gilford progeria, causes hypocontraction in mice. Interestingly, this aging feature can be counteracted by increased dietary nitrites [ 22 ]. Reduced vascular stiffness was proposed as a mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction of DNA repair capacity by targeted mutation of Lmna in VSMC, the gene that is responsible for accelerated-aging in Hutchinson–Gilford progeria, causes hypocontraction in mice. Interestingly, this aging feature can be counteracted by increased dietary nitrites [ 22 ]. Reduced vascular stiffness was proposed as a mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbed vasoconstriction is another feature of age-related vasomotor changes [6,[20][21][22]. KCl was chosen to study alterations in contractility because it is free of receptor-mediated signaling.…”
Section: Effect Of Sildenafil On Vasoconstriction Mediated By Kcl 100mentioning
confidence: 99%
See 1 more Smart Citation
“…The thoracic aorta of ≈14-week-old Lmna G609G/G609G mice shows no evidence of VSMC loss but does show reduced numbers of smooth muscle fibers (measured by hematoxylin staining) and increased deposition of medial collagen [ 51 ]. Moreover, vessel contraction in response to phenylephrine and potassium chloride is impaired in thoracic aorta segments from these progeroid mice [ 50 , 56 ], and this effect is not rescued by collagen disruption after collagenase treatment [ 50 ]. In line with this evidence of progressive damage, dysfunction, and dedifferentiation of VSMCs in Lmna G609G/G609G mice, atheroprone Apoe −/− Lmna G609G/G609G mice show VSMC depletion in the aortic arch at 16 weeks of age but not at 8 weeks [ 53 ].…”
Section: Role Of Vsmcs and Ecs In Hgps-associated Cardiovascular Dysfunctionmentioning
confidence: 99%
“…For instance, Park et al found that gastrin releasing peptide (GRP) diminished calcification in cultured vascular smooth muscle cells (VSMC), and its inhibition reverted the phosphate-induced calcium deposition in rodent models [ 19 ]. By using models of accelerated aging, Del Campo et al [ 20 ] identified VSMC as the main cellular type causing contractile impairment in a mouse model of Hutchinson-Gilford progeria syndrome (HGPS), and reported the beneficial effect of nitrite treatment. The impairment of vascular contractility is a part of the structural and functional alterations of the cardiovascular system in both physiological and premature aging, which in progeria patients, leads to accelerated arterial stiffness and atherosclerosis, and exaggerated CVD [ 21 ].…”
mentioning
confidence: 99%